Inorganic Chemical Approaches to Pharmacognosy. II. X-Ray Fluorescence Spectrometric Studies on the Inorganic Constituents of Crude Drugs. (1). On the Licorice Root - MINO, YOSHIKI; OTA, NAGAYO; TSUKIOKA, YASUYUKI (Chem. Pharm. Bull, 1984)
Inorganic constituents of many licorice roots (55 samples; almost all obtained commercially in Osaka market) were investigated using energy-dispersive X-ray fluorescence spectrometry. The results can be summarized as follows : (1) Most of the elemental contents of each licorice root showed considerable variation. (2) Many licorice roots contained Sr at a high level, and the contents of Sr and K were dependent on the geographical source of the root, i. e., the producing district (Seihoku or Tohoku). (3) The metals profile of each crude drug provides valuable information regarding the identification of not only the kind of crude drug but also the producing district or the original plant.